Regulatory T Cells Are Dispensable for Tolerance to RBC Antigens - Richards, Amanda L.; Kapp, Linda M.; Wang, Xiaohong; Howie, Heather L.; Hudson, Krystalyn E. (Frontiers in Immunology, 2016)
Autoimmune hemolytic anemia (AIHA) occurs when pathogenic autoantibodies against red blood cell (RBC) antigens are generated. Whilst the basic disease pathology of AIHA is well studied, the underlying mechanism(s) behind the failure in tolerance to RBC autoantigens are poorly understood. Thus, to investigate the tolerance mechanisms required for the establishment and maintenance of tolerance to RBC antigens, we developed a novel murine model. With this model, we evaluated the role of regulatory T cells (Tregs) in tolerance to RBC-specific antigens. Herein, we show that neither sustained depletion of Tregs nor immunization with RBC-specific proteins in conjunction with Treg depletion led to RBC-specific autoantibody generation. Thus, these studies demonstrate that Tregs are not required to prevent autoantibodies to RBCs and suggest that other tolerance mechanisms are likely involved.